2021
DOI: 10.2340/16501977-2799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tai chi on glycaemic control, lipid metabolism and body composition in adults with type 2 diabetes: A meta-analysis and systematic review

Abstract: Objective The aim of this systematic review was to evaluate the effects of tai chi on metabolic control and body composition indicators in patients with type 2 diabetes mellitus. Design Systematic review and meta-analysis of existing literature. Methods Electronic resource databases were searched to collect eligible studies. Two reviewers selected studies and independently evaluated methodological quality. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Tai chi has been reported to alleviate the lipid profile disorders in other conditions [31][32][33][34], which was also observed in this trial. A significant difference was observed between the two intervention groups in TC, TG, and LDL-C. BMI and HOMA-IR were also decreased in the Tai chi group, which seems consistent with reports that Tai chi could contribute to weight loss and improve insulin resistance [35], and the effect seemed similar to other aerobic exercises [36].…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 78%
“…Tai chi has been reported to alleviate the lipid profile disorders in other conditions [31][32][33][34], which was also observed in this trial. A significant difference was observed between the two intervention groups in TC, TG, and LDL-C. BMI and HOMA-IR were also decreased in the Tai chi group, which seems consistent with reports that Tai chi could contribute to weight loss and improve insulin resistance [35], and the effect seemed similar to other aerobic exercises [36].…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 78%
“…After reading the full text, 6 articles [25][26][27][28][29][30] were found irrelevant to SRs/MAs in RCTs, and 2 SRs/MAs [31,32] were not about people with T2DM. Thus, 8 SRs/MAs [33][34][35][36][37][38][39][40] were finally included in this overview. The process of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics included in the overview are shown in Table 2. These SRs/ MAs were all published between 2017 and 2021, 5 [33][34][35][36][37] of which were in English, and the remaining 3 [38][39][40] were in Chinese. One [34] of the SRs/MAs was published by Korean researchers, and the remaining 7 SRs/MAs [33,[35][36][37][38][39][40] were published by Chinese researchers.…”
Section: Description Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Tai Chi is beneficial in improving older person’s physical and psychological well-being. Evidence from clinical data have identified Tai Chi plays an important role in improving chronic diseases such as hypertension [ 4 ], chronic obstructive pulmonary disease and chronic heart failure [ 5 ], preventing falls [ 6 ], controlling blood glucose [ 7 ], and alleviating psychological symptoms such as depression and anxiety [ 8 10 ] in the old peoples.…”
Section: Introductionmentioning
confidence: 99%